Preparation of kenaf derived cellulose-filled polylactic acid composites - Mohamed Amin Tawakkal, Intan Syafinaz (2011)
The aim of current research was to prepare kenaf derived cellulose (KDC)/polylactic acid (PLA) composites. The KDC or α-cellulose was derived from kenaf bast fibre (KBF) which was chemically treated via chlorination and mercerisation processes. The characteristics of kenaf fibre and cellulose on the chemical, morphological and physical properties were investigated by using FTIR, ESEM and density measurements. Optimisation of the composite processing variables namely temperature and time was carried out via RSM with respect to tensile strength and stock temperature. The composites were compounded using internal mixer at fixed KDC loading of 5 wt% and screw speed of 50 rpm in the temperature range of 160, 170 and 180°C for 10, 20 and 30 minutes. The effects of various KDC loadings (0-60 wt%) on the chemical, mechanical, thermal and physical properties of the KDC/PLA composites were also investigated. The cellulose was successfully derived from the KBF by removing of lignin and hemicellulose. This was confirmed by the absence of these components from the FTIR spectrum of the cellulose and the ESEM micrographs. From the ESEM micrographs, the cellulose could be observed by its greater size reduction than the raw fibre and rough surface topography. Meanwhile, the ANOVA statistical data demonstrated that the tensile strength and stock temperature of the 5 wt% KDC/PLA composites were affected mostly by mixing temperature with P < 0.0500. The composites performed an optimum value at two combinations of variables which are at 170°C for 20 minutes and 170°C for 30 minutes. Nevertheless, 170°C and 30 minutes was chosen as the best mixing conditions in order to produce composite at higher KDC loading. The FTIR spectrum of the KDC/PLA composite clearly indicated that no chemical interaction was present between KDC and PLA matrix in the composite. Interestingly, the incorporation of KDC into PLA matrix has demonstrated remarkable improvement in the tensile strength and stiffness properties. The tensile strength and modulus of KDC/PLA composite increased as the KDC loading increased. The ESEM micrographs revealed evidence of good interfacial adhesion between the KDC and PLA matrix and even distribution of the KDC in the composite system. However, the effects of KDC loading on the flexural and notched impact strength indicated that no remarkable changes were occurred in a range of 10 to 40 wt% of KDC loading. The incorporation of the KDC into PLA matrix also improves the stiffness of composite due to the enhancement of storage modulus as compared to the neat PLA. The DMA results demonstrated that the storage modulus of the 60 wt% KDC/PLA composite is twice higher than the neat PLA and the rest of the composites within a high temperature range (above 80°C). The glass transition temperatures (Tg) generated from the loss modulus curves exhibit that the peak was shifted to higher temperature as the percentage of cellulose loading in the composites was increased. Thus, the addition of KDC into the PLA matrix resulted better thermal stability and exhibited effective reinforcing agent. The water absorption of the composites increased with increasing KDC loading while the neat PLA absorbed lesser water. The 60 wt% KDC/PLA composite demonstrated approximately 12% of water uptake, which is considered as relatively low percentage of water absorption in biocomposite.